The effectiveness of personal budgets for people with mental health problems: a systematic review. (June 2014) - Webber, Martin; Treacy, Samantha; Carr, Sarah; Clark, Mike; Parker, Gillian
Abstract Background: Personal budgets are a key policy priority in adult social care in England and are expected to become increasingly important in the care of adults with mental health problems. Aims: This article systematically reviews evidence for the effectiveness of personal budgets for people with mental health problems across diverse outcomes. Methods: The review, conducted in 2013, used the EPPI-Centre methodology for conducting a systematic review informed by Social Care Institute for Excellence guidelines. Data were extracted from studies and combined using meta-synthesis. Results: Fifteen studies were included in the review which found mostly positive outcomes in terms of choice and control, quality of life, service use and cost-effectiveness. However, methodological limitations make these findings rather unreliable and insufficient to inform personal budgets policy and practice for mental health service users. Conclusions: Further high quality studies are required to inform policy and practice for mental health service users, which lags behind other adult social care groups in the use of personal budgets.